1999
DOI: 10.1063/1.478558
|View full text |Cite
|
Sign up to set email alerts
|

Nematic–isotropic transition in polydisperse systems of infinitely thin hard platelets

Abstract: We study the phase behavior of model colloidal systems composed of infinitely thin hard platelets, with polydispersity in the size of the particles. Semi-grand Gibbs ensemble simulations are used to study the coexisting nematic and isotropic phases for a range of systems with varying polydispersity. Particle size segregation is observed in the two coexisting phases, with the larger particles tending to be found in the nematic phase. This fractionation becomes more evident with increasing polydispersity. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
162
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 26 publications
14
162
0
Order By: Relevance
“…Computer simulations of monodisperse, infinitely thin platelets have shown that the coexisting densities and pressure at the I-N transition are 16 where n I and n N are the number densities of platelets in the isotropic and the nematic phase, respectively, and Π ) ΠD 3 / kT is the reduced osmotic pressure. On the other hand, in the case of platelets with a finite thickness (D/L ) 10) these quantities are…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Computer simulations of monodisperse, infinitely thin platelets have shown that the coexisting densities and pressure at the I-N transition are 16 where n I and n N are the number densities of platelets in the isotropic and the nematic phase, respectively, and Π ) ΠD 3 / kT is the reduced osmotic pressure. On the other hand, in the case of platelets with a finite thickness (D/L ) 10) these quantities are…”
Section: Discussionmentioning
confidence: 99%
“…The computer simulation data showed that the width of the coexistence region depends quadratically on the polydispersity in diameter. 16 Yet, size segregation between the coexisting phases is weak in both experiment and simulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, phase-separating colloidal systems, of spheres [46,[61][62][63] or platelets [59,60,64,65], deal with this by fractionation of the particles between the phases, leading to sub-phases with a (slightly) smaller polydispersity than the parent suspension. In sample C, where non-adsorbing polymer enhances fractionation even more, this lowering of the polydispersity facilitates the formation of the single columnar crystal.…”
mentioning
confidence: 99%